EFFECT OF PROFITABILITY, LEVERAGE AND LIQUIDITY AGAINST FINANCIAL DISTRESS (CASE STUDY OF FOOD SUBSECTOR MANUFACTURING COMPANY AND BEVERAGE LISTED ON IDX FOR THE 2018-2022 PERIOD) - Marcell Gilbert Immanuel; Afrizal Nilwan; Haninun (ZILLZELL MEDIA PRIMA, 2024)
The purpose of this study is to determine the impact of profitability (X1), leverage (X2), and liquidity (X3) on financial distress (Y) in food and beverage (F&B) companies on the Indonesia Stock Exchange (IDX) during the 2018-2022 period. Profitability (X1) is measured by ROA, leverage (X2) using DAR and liquidity (X3) by CR value. This research uses quantitative methodology with the population of food & beverage companies that have been listed on the Indonesia Stock Exchange from 2018 to 2022. The sampling procedure used a purposive sampling strategy and resulted in a total of 16 food and beverage companies as research samples. Data analysis using multiple linear regression models. The findings of this research show that the financial distress (Y) experienced by food and beverage manufacturing companies in the 2018-2022 period was significantly influenced by profitability (X1), leverage (X2) and liquidity (X3) positively.